PWE-099 Premature dissolution of the agile patency device. (8th June 2018) - Wray, Nicholas; Healy, Ailish; Thurston, Victoria; Zammit, Stefania; Tai, David; Ching, Hey-Long; Hale, Melissa; Sidhu, Reena; Blakeborough, Tony; McAlindon, Mark
Abstract : Introduction: Confirmed (visual) passage of an intact Agile (Medtronic Ltd) patency device (which contains a radiofrequency (RF) tag), absence of an RF signal or failure to identify the patency device on radiological imaging 30 hours post-ingestion predicts safe capsule endoscopy. [Hererrias et al., Gastrointest Endosc 2008] Premature dissolution of the device would give false reassurance that capsule endoscopy could be performed safely. Methods: Retrospective review of 2017 patency capsule database. Results: RF scan was performed on 490 patients 30 hours after swallowing an Agile patency device and, if an RF signal was present, patients went for a scout film and, where indicated, limited CT scan. Premature dissolution occurred in four cases (0.8%). All had normal colonoscopies and symptoms of Crohn's disease (two of whom had abnormal, one normal and one no prior small bowel imaging). In two, the scout films were reported normal, but a persistent RF signal prompted re-examination of the films and the identification of the RF tags. In the two later cases, the RF tag alone or with adjacent high density material (consistent with barium) was recognised as demonstrating premature dissolution. Conclusions: This is the first report of premature dissolution of the Agile patency device which occurred in about 1:100 cases. If the RF signal remains 30 hours post ingestion, care should be taken to look for the RF device on radiological imaging when the intact patency device (see figure 1) is not evident. The tags may be confused with surgical clips, IUCDs, metallic items of clothing and jewellery.